Analysis of the factors influencing the precooling process of cryogenic compressed hydrogen storage tank. Issue 1 (1st May 2022) - He, M; Jia, Q M; Lv, C; Wu, J H; Zhang, Y; Zhu, W P; Zhang, M M; Gong, L H
Abstract: Cryogenic compressed hydrogen has attracted much attention recently. Its volume and weight hydrogen storage density are relatively high, which can meet the long-distance driving demand of hydrogen fuel cell vehicles. It is considered as a very promising physical storage method. In the process of transportation, the precooling process of cryogenic compressed hydrogen storage tank is very important. It is necessary to establish a reasonable mathematical model, analyse the precooling process of the storage tank theoretically, and use the hydrodynamics software for numerical simulation to analyse the influencing factors of the precooling process. On the basis of theoretical analysis, this paper uses ANSYS FLUENT software to simulate the precooling process of intake pipe length, intake pipe diameter, length diameter ratio of storage tank, insulation performance of high vacuum multilayer insulation material, lining material, initial temperature of storage tank and hydrogen filling rate. By comparing the distribution of internal temperature field and enclosure temperature field as well as precooling time, the design suggestions of Cryogenic compressed hydrogen storage tank and hydrogenation suggestions are given.